GAMBARAN GANGGUAN TIDUR PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Bayu Prasetyo (2022)
College students are at an important stage in their need for sleep to increase their concentration levels. Sleep disturbance is a complaint that often occurs in students, especially medical students. In previous studies, only one type of sleep disorder was conducted Methods: This research is a cross-sectional study. Data collection was carried out using the Sleep-50 Questionnaire questionnaire developed by Spoormaker which would then be carried out by univariate analysis. Respondents in the study were all students of the Faculty of Medicine at the Jakarta Veterans National Development University as many as 465 respondents Results: Out of a total of 581 respondents, 91% experienced one sleep disorder. 225 respondents (38.7%) had sleep apnea, 348 respondents (59.9%) had insomnia, 465 respondents (80%) had narcolepsy, 187 respondents (32.2%) had restless legs or PLMD, 309 respondents (53 .2%) experienced circadian rhythm sleep disorders, 16 respondents (2.8%) experienced sleep walking, 67 respondents (11.5%) experienced nightmares or nightmares Conclusion: Sleep disorders are common among medical students, especially narcolepsy, insomnia and sleep disorders related to circadian rhythms. It is very important to detect and treat it before the condition gets worse.